2022
DOI: 10.1177/2156759x221126686
|View full text |Cite
|
Sign up to set email alerts
|

Novice School Counselors’ Burnout Profiles and Professional Experiences: A Mixed-Methods Study

Abstract: This convergent mixed-methods study examined the distinct burnout profiles of novice school counselors and their respective professional experiences. A cluster analysis yielded a three-factor solution revealing unique burnout profiles. Qualitative analyses identified job-related challenges and resources impacting the work performance of novice school counselors. We provide recommendations for school counselor training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Specific to the issue of being assigned large student caseloads (ASCA, 2021), Mullen et al (2021) found that "school counselors with lower ratios or caseloads of students reported experiencing lower levels of burnout and job stress and higher levels of job satisfaction" (p. 33). Similarly, Bardhoshi et al (2022) found that novice school counselors with caseloads below 250 students reported lower burnout than those with caseloads above this threshold.…”
Section: School Counselor Burnoutmentioning
confidence: 88%
See 1 more Smart Citation
“…Specific to the issue of being assigned large student caseloads (ASCA, 2021), Mullen et al (2021) found that "school counselors with lower ratios or caseloads of students reported experiencing lower levels of burnout and job stress and higher levels of job satisfaction" (p. 33). Similarly, Bardhoshi et al (2022) found that novice school counselors with caseloads below 250 students reported lower burnout than those with caseloads above this threshold.…”
Section: School Counselor Burnoutmentioning
confidence: 88%
“…In determining the primary sources of stress for school counselors, Maor and Hemi (2021) described how the assignment of non-counseling-related/inappropriate duties were perceived as more stressful than counseling role duties. Further, Bardhoshi et al (2022) described how a “negative work environment is an important dimension of counselor burnout” (p. 9) and reported that participants in their study listed non-counseling duties, high caseloads, and unclear job duties/expectations as contributors to burnout. Fye et al (2020) found that having fewer years of experience as a school counselor was associated with certain dimensions of burnout, including feelings of incompetence and devaluating clients.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, our investigation of student-to-schoolcounselor ratio as an outcome variable (RQs 1 and 2) shed light on school counselor-and school-level factors related to achieving an ASCA recommended student-to-school-counselor ratio of less than or equal to 250:1. In considering this ratio as an independent variable (RQ3) per se, this study also expands the literature to illuminate how caseloads may be related to school counselors' leadership practices (Bardhoshi et al, 2022;Mullen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, there has been a growing number of studies that supported the pervasiveness of counselor burnout (as measured by the CBI) in different counseling disciplines over the past 15 years, such as school counseling (Bardhoshi, 2012), clinical mental health counseling (Puig et al, 2012), addiction counseling (Wallace et al, 2010), marriage and family counseling (R. Chen et al, 2019), and rehabilitation counseling (O'Sullivan & Bates, 2014). Gnilka et al (2015) discussed the importance of comparing burnout scores (using the CBI) across different counseling disciplines to illuminate the nuances of burnout factors.…”
Section: Discussionmentioning
confidence: 99%
“…Following this seminal work on the CBI, many researchers have applied this scale to explore counselor burnout. For example, Bardhoshi (2012) examined the relationship between burnout and taking non-counseling duties among professional school counselors. Wallace et al (2010) investigated job stress, coping strategies, and burnout among abuse-specific counselors.…”
Section: Introductionmentioning
confidence: 99%